Differentiated Learning Approach Model in Inclusive Classrooms Based on Social Emotional Learning in Elementary School - Rahmah, Siti; Rasmitadila; Amril, La Ode (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Inclusive education in elementary schools requires instructional practices that accommodate students’ diverse characteristics, both in academic and social emotional aspects; however, classroom practices indicate that the implementation of differentiated instruction remains suboptimal and is still predominantly focused on cognitive outcomes without systematically integrating Social Emotional Learning (SEL). This study aims to develop a differentiated instruction model for inclusive classrooms based on Social Emotional Learning that is valid, practical, and applicable in elementary schools. The research employed a Research and Development (R&D) method using a Design-Based Research (DBR) approach through three stages: analysis and exploration, design and construction, and evaluation and reflection. The participants involved principals and teachers from inclusive elementary schools in Bogor Regency and Bogor City selected through purposive sampling. Data were collected through semi-structured interviews, observations, document analysis, expert validation, and practicality questionnaires, and were analyzed using thematic analysis, needs analysis, content validity analysis, and descriptive quantitative analysis. The f indings revealed that teachers encountered difficulties in mapping students’ characteristics and integrating social-emotional aspects into instructional practices; therefore, a model was developed incorporating holistic academic and social-emotional needs assessment, differentiation of content, process, and product, and the establishment of an inclusive and supportive classroom climate. Expert validation and limited field testing indicated that the model met the criteria of validity and practicality and assisted teachers in designing more systematic and responsive instruction for diverse learners. In conclusion, the developed model offers both a conceptual and operational solution to strengthen holistic, equitable, and humanistic inclusive teaching practices in elementary schools